A comparisons of academic achievement between a rural school and an urban school in Malaysia - Mee, Leonard Yong; Ho, Keng Heng.
Since rural students are generally believed to perform lower than their urban counterparts, the main purpose of this study is to examine whether such differences in academic achievement are significant. It is intended to compare the academic achievements of rural school and an urban school while controlling for differences in size of enrolment and availability of facilities in the schools.
Keywords: Academic achievement -- Malaysia -- Muar (Johor).; Rural schools -- Malaysia -- Muar (Johor).; Urban schools -- Malaysia -- Muar (Johor).